Performance of the CITA almond releases and some elite breeding selections - Alonso Segura J.M.; Socias i Company R.; Kodad O.; Espada Carbó J.L.; Andreu Lahoz J.; Escartín Santolaria J. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Almond growing is lately increasing in Spain due to higher kernel prices and better orchard management techniques, making this crop more profitable and attractive. In addition, the release of more productive, extra-late blooming and fully autogamous cultivars, is allowing the shift of almond growing to inland areas with colder climates. The release of new cultivars must be based on their agronomic behavior under different climatic conditions. Consequently, the performance of the last commercial CITA almond cultivars (‘Guara’, ‘Soleta’, ‘Isabelona’, ‘Diamar’ and ‘Vialfas’) and some breeding selections (‘G-3-3’, ‘G-3-4’, ‘G-5-25’, ‘G-2-22’ and ‘I-3-67’) was studied in a trial at the “AFRUCCAS Experimental Fruit Farm” near Caspe (Zaragoza, Spain). The trial was established in 2005 at a distance of 6 x 7m on the peach x almond INRA GF-677 rootstock. Scions were grafted in 2006 and the trees were trained as free open vase and managed under usual commercial requirements and drip irrigation. Phenology, vigor, production, fruit and orchard parameters were controlled to ascertain the agronomical performance of each cultivar or selection. The success of any cultivar not only depends of the accuracy of the breeder’s selection, but also its adaptability must be ascertained to be recommended in a specific region.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)